Nitrate, Phosphate, Silica and Phytoplankton Abundance in the Coastal Waters of Maitara Island, North Maluku - Sabar, Mesrawaty; Samman, Ardan; Abubakar, Salim; Sunarti, Sunarti; Rina, Rina; Bahtiar, Bahtiar (Journal Omni-Akuatika, 2024)
Nitrate, phosphate, and silica are nutrients needed for the growth of phytoplankton populations. The primary objective of the present study was to establish the relationship between the nutrient composition (nitrate, phosphate, and silica) and phytoplankton abundance. Sampling was was conducted at three observation stations located in the tidal zone of Maitara Island coast, North Maluku. Collection of plankton samples in coastal waters using a 25 µm plankton net. Phytoplankton cells were identified and counted in the laboratory using an electric microscope with 100x magnification. Phytoplankton observations were carried out using the field of view method. Testing the concentration of nitrate, phosphate, and silica using spectrophotometer techniques. The research data were analyzed using a correlation test. The research findings indicated that the coastal waters surrounding Maitara Island were classified as oligotrophic waters, based on the nitrate and phosphate, and silica content. Oligotrophic waters have very low nutrient content such as nitrogen and phosphorus, causing low primary productivity. Simultaneously, nitrate, phosphate, and silica concentrations had a very strong correlation (R=0.823) with phytoplankton abundance. Partially, the correlation between nitrate concentration and phytoplankton abundance was classified as very strong (R=0.729). However, the correlation between phosphate concentration and phytoplankton abundance was moderately significant (R=0.577), and the correlation between silica concentration and phytoplankton abundance was weak (R=0.386). High concentrations of nitrate and phosphate in coastal waters lead to increased abundance of phytoplankton. However, high silica concentrations in waters can only increase the abundance of certain phytoplankton groups, for example diatoms and radiolarians. Keywords: Phytoplankton abundance, nitrate, phosphate, silica, Maitara Island